Knowledge and attitude of mental health professionals towards psychodrama as a psychotherapeutic tool - Nupur Mahatme; Anil Kakunje; Dilshana Nafisa; Jeyaram Srinivasan; Sowmya Puthran; Jochen Becker Ebel (Telangana Journal of Psychiatry, 2018)
Aim: To understand the attitude and knowledge of mental health professionals towards psychodrama. Materials and Methods: Knowledge and attitude towards psychodrama was studied during a basic psychodrama workshop for 30 mental health professionals, which included psychiatrists, residents of psychiatry, psychologists, social workers and mental health nurses. A specially designed 10 item questionnaire was used for a pre and post-test which evaluated on various aspects of psychodrama to know the attitude and knowledge towards this unique therapeutic tool. Participants were asked to rate their experience of the psychodrama session. Written informed consent was taken from all participants. Results and Discussion: Results showed that in all 10 questions there was a marked, positive change in the post test results. The 3 hours basic course made an impact on attitude and knowledge of psychodrama of all participants. The acceptance of the session, by the participants, delivered an average score of 7.8 on a 10 point scale. Conclusion: Mental health professionals must necessarily undergo workshops on psychodrama in order to bring about positive and impactful results in their clinical applications, which would go a long way in effective clinical therapies. Psychodrama with proper training can have a wide range of clinical applications in various psychiatric settings.